Non-conductive film, semiconductor device, and method for manufacturing same
By using the adhesive layer of thermoplastic resin, thermoset resin and inorganic filler in semiconductor manufacturing, the Y value is calculated to be 3 or less, which solves the void problem in semiconductor manufacturing and improves the reliability of the semiconductor device.
Patent Information
- Application Number
- CN202380015667.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-18
- Filing Date
- 2023-11-08
- Publication Date
- 2024-12-20
AI Technical Summary
In the semiconductor manufacturing process, the prior art is difficult to prevent the creation of voids in the sealing layer, affecting the reliability of the semiconductor device, especially in the hot press bonding process in the flip chip installation method.
An adhesive layer containing a thermoplastic resin, a thermosetting resin, a curing agent and an inorganic filler is used to calculate the adhesive layer with a Y value of 3 or less through specific compositional proportions and process processing to prevent the generation of voids.
It effectively prevents voids during semiconductor manufacturing and hot press bonding, and improves the reliability and sealing performance of semiconductor devices.
Smart Images

Figure BDA0004912466880000131 
Figure BDA0004912466880000151 
Figure BDA0004912466880000161
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0050688 filed in the Korean Intellectual Property Office on April 18, 2023, the disclosure of which is incorporated herein by reference in its entirety.
[0003] The present invention relates to a non-conductive film, a semiconductor device and a method for manufacturing the same. Background Art
[0004] Recently, as the trend toward miniaturization, higher functionality, and greater capacity of electronic devices expands, the demand for higher density and higher integration of semiconductor packages has rapidly increased.
[0005] In response to such a demand, a flip chip mounting method has been introduced to directly connect a semiconductor element such as a semiconductor chip to a substrate. In the flip chip mounting method, the semiconductor chip is electrically connected to other semiconductor chips, wiring boards, etc. through solder bumps formed on the semiconductor chip. At this time, an underfill material is filled between the bonding surfaces to strengthen the bonding position and improve the bonding reliability.
[0006] As such an underfill filling method, a capillary underfill method is known. However, the capillary underfill method has a fundamental problem that it is difficult to uniformly inject the underfill material into the tiny space between electrodes in a short period of time. In addition, in recent years, as the spacing between electrodes becomes narrower and the thickness of semiconductor chips becomes thinner, the capillary underfill method has its limitations in providing a sealing layer with a uniform thickness.
[0007] Therefore, a method using a non-conductive film has been developed. According to this method, a non-conductive film is formed or attached to the element forming surface of a semiconductor wafer, the semiconductor wafer is cut and individualized into semiconductor chips, and then the individualized semiconductor chips are mounted on a substrate and metal bonding and sealing are performed at the same time.
[0008] This metal bonding and sealing is mainly performed by a thermocompression bonding (TCB) method. The thermocompression bonding method can be performed by applying pressure for a short period of time of about 2 seconds to 10 seconds at a temperature of about 200°C to 300°C. Since the thermocompression bonding method involves rapid changes in temperature and pressure, there is a problem that voids are easily generated in the sealing layer formed by the non-conductive film. However, if the voids are retained in the sealing layer without being removed, it will adversely affect the reliability of the semiconductor device. Summary of the invention
[0009] Technical issues
[0010] An object of the present invention is to provide a non-conductive film that prevents the generation of voids during a semiconductor manufacturing process.
[0011] Another object of the present invention is to provide a semiconductor device including the non-conductive film.
[0012] Still another object of the present invention is to provide a method for manufacturing a semiconductor device.
[0013] Technical Solution
[0014] Now, a non-conductive film, a semiconductor device, a method of manufacturing the semiconductor device, and the like according to specific embodiments of the present invention will be described.
[0015] According to one embodiment of the present invention, there is provided a non-conductive film, the non-conductive film comprising an adhesive layer, the adhesive layer comprising a thermoplastic resin, a thermosetting resin, a curing agent and an inorganic filler, wherein Y of the following equation 1 of the adhesive layer is greater than 0 and is 3 or less:
[0016] [Equation 1]
[0017] Y=(△T*G) 2 / (5.88*η)
[0018] Where, in equation 1,
[0019] ΔT is the difference between the heat generation starting temperature and the maximum heat generation temperature of the adhesive layer measured by differential scanning calorimetry at a heating rate of 10°C / min and a temperature of 30°C to 300°C, G is the gel time at 200°C measured in seconds for the adhesive layer, and η is the minimum melt viscosity measured in Pa·seconds for the adhesive layer.
[0020] The non-conductive film of one embodiment may be a non-conductive film used before a semiconductor manufacturing process, a non-conductive film applied during a semiconductor manufacturing process, or a non-conductive film included in a final semiconductor device.
[0021] The non-conductive film used before the semiconductor manufacturing process may mean a film including a B-stage adhesive layer applied to a substrate. In one example, the non-conductive film used before the semiconductor manufacturing process may be a die attach film in which a substrate and an adhesive layer are laminated, or a dicing die bonding film in which a substrate, a pressure-sensitive adhesive layer, and an adhesive layer are sequentially laminated.
[0022] The non-conductive film applied during the semiconductor manufacturing process may refer to a B-stage adhesive layer applied to a semiconductor element. In other words, the non-conductive film may be applied to a substrate, produced in a film-forming form, and then attached to a semiconductor element, but a film-forming form may be produced by applying an adhesive composition to a semiconductor element.
[0023] The non-conductive film included in the final semiconductor device may mean a cured adhesive layer present in the final semiconductor device manufactured through a semiconductor manufacturing process. The cured adhesive layer may be a sealing layer that seals a semiconductor element.
[0024] In Equation 1, a value calculated in the unit of ° C is substituted into ΔT, a value measured in seconds (sec) is substituted into G, and a value measured in the unit of Pa·second is substituted into η. However, by omitting the unit and substituting only the numerical value, Y in Equation 1 can be calculated as a value without a unit.
[0025] When a non-conductive film including an adhesive layer in which Y calculated by Equation 1 is 3 or less is used in a semiconductor manufacturing process, voids are not easily generated, and a semiconductor device with excellent reliability can be provided. In particular, the non-conductive film including an adhesive layer in which Y calculated by Equation 1 is 3 or less can effectively prevent the generation of voids even in a thermal compression bonding process of a flip chip mounting method in which voids are easily generated, thereby providing a semiconductor device with excellent reliability.
[0026] An adhesive layer for bonding components of semiconductor devices having different linear expansion coefficients, etc. (e.g., a wiring board and a semiconductor chip, different semiconductor chips, etc.) needs to protrude sufficiently around the bonded components to form a fillet, thereby dispersing stress generated in the components due to temperature changes and improving reliability. A non-conductive film including an adhesive layer in which Y calculated by Equation 1 is 3 or less can form a fillet in an amount suitable for ensuring the reliability of the semiconductor device, and in particular, can effectively prevent the generation of voids in the fillet.
[0027] ΔT in Equation 1 is the difference between the heat generation start temperature and the maximum heat generation temperature of the adhesive layer. For a specific measurement method of ΔT, refer to the details described in the test examples described later.
[0028] ΔT may be a value determined based on the gel time and the minimum melt viscosity so that Y in Equation 1 is 3 or less. In one example, ΔT may be 1°C to 20°C. More specifically, ΔT may be 1°C or more, 2°C or more, 3°C or more, 4°C or more, 5°C or more, 6°C or more, or 7°C or more, and 20°C or less, 15°C or less, 14°C or less, 13°C or less, 12°C or less, 11°C or less, or 10°C or less. When the adhesive layer is cured at an appropriate rate during the thermocompression bonding process within this range, additional voids can be prevented from being generated inside while ensuring sufficient time for the voids to escape.
[0029] G in Equation 1 is the gel time of the adhesive layer at 200° C. G is the gel time of the B-stage adhesive layer, and for a specific measurement method, refer to the details described in the test examples described later.
[0030] G can be a value determined according to ΔT and the minimum melt viscosity so that Y in equation 1 is 3 or less. In an example, G can be 5 seconds to 30 seconds. More specifically, G can be 5 seconds or more, 6 seconds or more, 7 seconds or more, and 30 seconds or less, 20 seconds or less, 10 seconds or less, 9 seconds or less, 8.5 seconds or less, 8.3 seconds or less, 8.2 seconds or less, or 8.14 seconds or less. When the adhesive layer is cured at an appropriate rate during the thermocompression bonding process within this range, it is possible to prevent the generation of additional voids inside, while ensuring sufficient time for the voids to escape.
[0031] η in Equation 1 is the minimum melt viscosity of the adhesive layer. For a specific measurement method of η, refer to the details described in the test examples described later.
[0032] η can be a value determined according to ΔT and gel time so that Y in equation 1 is 3 or less. In one example, η can be 10Pa·seconds to 5000Pa·seconds. More specifically, η can be 10Pa·seconds or more, 50Pa·seconds or more, 100Pa·seconds or more, 150Pa·seconds or more, 200Pa·seconds or more, 250Pa·seconds or more, 300Pa·seconds or more, 350Pa·seconds or more, or 400Pa·seconds or more, and 5000Pa·seconds or less, 4000Pa·seconds or less, 3000Pa·seconds or less, 2000Pa·seconds or less, 1000Pa·seconds or less, 900Pa·seconds or less, 800Pa·seconds or less, or 700Pa·seconds or less. Within this range, the adhesive layer can exhibit appropriate fluidity to fully embed the semiconductor element in a state where voids are unlikely to be generated.
[0033] Y in Equation 1 is a factor related to the generation of voids due to the adhesive layer during the semiconductor manufacturing process, and when the value of Y is 3 or less, the generation of voids can be effectively suppressed. More specifically, Y in Equation 1 may be 3 or less, 2.5 or less, 2 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, or 1.5 or less. Y in Equation 1 is a value greater than 0, and for example, it may be 0.00001 or more, 0.001 or more, 0.001 or more, 0.1 or more, 0.5 or more, 0.8 or more, or 1 or more.
[0034] The adhesive layer according to one embodiment may include a thermoplastic resin, a thermosetting resin, a curing agent, and an inorganic filler.
[0035] The adhesive layer according to one embodiment is a thermoplastic resin, and may include two or more thermoplastic resins having different glass transition temperatures. In this case, it is advantageous to provide an adhesive layer in which Y in Equation 1 is 3 or less.
[0036] Specifically, the thermoplastic resin may include a first thermoplastic resin having a glass transition temperature of -10°C to 50°C and a second thermoplastic resin having a glass transition temperature of more than 50°C and 100°C or less.
[0037] The type of the first thermoplastic resin is not particularly limited, and examples thereof may include one or more resins selected from the following: polyimide-based resins, polyetherimide-based resins, polyesterimide-based resins, polyamide-based resins, polyethersulfone-based resins, polyetherketone-based resins, polyolefin-based resins, polyvinyl chloride-based resins, phenoxy-based resins, butadiene-based rubbers, styrene-butadiene-based rubbers, modified butadiene-based rubbers, reactive butadiene acrylonitrile copolymer rubbers, and (meth)acrylate-based resins.
[0038] In one example, the first thermoplastic resin may include a resin based on (meth) acrylate. The resin based on (meth) acrylate may be a (co)polymer produced by one or more monomers, and the one or more monomers are selected from: (meth) acrylic acid C1-12 alkyl esters, (meth) acrylic acid esters containing reactive functional groups, acrylonitrile and vinyl-based monomers that can be polymerized therewith. (Meth) acrylic acid C1-12 alkyl esters may include, for example, ethyl (meth) acrylate, propyl (meth) acrylate, butyl (meth) acrylate, pentyl (meth) acrylate, hexyl (meth) acrylate, heptyl (meth) acrylate or octyl (ethyl hexyl (meth) acrylate) etc. (meth) acrylate containing reactive functional groups may include, for example, monomers containing at least one of epoxy, hydroxyl and carboxyl. Specifically, (meth) acrylate containing reactive functional groups may include glycidyl (meth) acrylate. Vinyl monomers may include, for example, styrene etc.
[0039] In one example, the first thermoplastic resin may be a first copolymer produced from C1-12 alkyl (meth)acrylate, (meth)acrylate containing an epoxy group, and acrylonitrile.
[0040] For example, based on total repeating units, the first copolymer can include the repeating unit of (methyl) acrylic acid C1-12 alkyl ester with an amount of 30 wt % to 99 wt %, 50 wt % to 97 wt % or 60 wt % to 95 wt %. For example, based on total repeating units, the first copolymer can include the repeating unit containing epoxy group(s) with an amount of 0.1 wt % to 30 wt %, 0.1 wt % to 20 wt %, 0.1 wt % to 10 wt % or 0.1 wt % to 7 wt %. For example, based on total repeating units, the first copolymer can include the repeating unit of acrylonitrile with an amount of 1 wt % to 60 wt %, 5 wt % to 50 wt % or 7 wt % to 35 wt %.
[0041] The first thermoplastic resin may have a weight average molecular weight of 50,000 g / mol to 1,000,000 g / mol.
[0042] The first thermoplastic resin may have a glass transition temperature of -10°C or higher, -8°C or higher, or -6°C or higher, and 50°C or lower, 45°C or lower, or 42°C or lower. Within this range, it can be combined with the second thermoplastic resin, allowing Y in Equation 1 to have a lower value.
[0043] The type of the second thermoplastic resin is not particularly limited, but may include, for example, one or more resins selected from the group consisting of polyimide-based resins, polyetherimide-based resins, polyesterimide-based resins, polyamide-based resins, polyethersulfone-based resins, polyetherketone-based resins, polyolefin-based resins, polyvinyl chloride-based resins, phenoxy-based resins, butadiene-based rubbers, styrene-butadiene-based rubbers, modified butadiene-based rubbers, reactive butadiene acrylonitrile copolymer rubbers, and (meth)acrylate-based resins.
[0044] In one example, the second thermoplastic resin may include one or more resins selected from the group consisting of a (meth)acrylate-based resin and a phenoxy-based resin.
[0045] The resin based on (meth)acrylate can be a (co)polymer produced by one or more monomers, and the one or more monomers are selected from: (meth)acrylate C1-12 alkyl esters, (meth)acrylates containing reactive functional groups, acrylonitrile and vinyl-based monomers polymerizable therewith. (Meth)acrylate C1-12 alkyl esters can include, for example, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate (ethylhexyl (meth)acrylate), etc. The (meth)acrylate containing reactive functional groups can include, for example, monomers containing at least one of epoxy, hydroxyl and carboxyl groups. Specifically, the (meth)acrylate containing reactive functional groups can include glycidyl (meth)acrylate. Vinyl monomers can include, for example, styrene, etc.
[0046] In one example, the second thermoplastic resin may include a second copolymer derived from C1-12 alkyl (meth)acrylate, (meth)acrylate containing an epoxy group, acrylonitrile, and styrene.
[0047] For example, based on total repeating units, the second copolymer can include the repeating unit of (methyl) acrylic acid C1-12 alkyl ester with an amount of 20 % by weight to 60 % by weight or 30 % by weight to 50 % by weight. For example, based on total repeating units, the second copolymer can include the repeating unit containing epoxy group(ing) with an amount of 0.1 % by weight to 30 % by weight, 0.1 % by weight to 20 % by weight, 0.1 % by weight to 10 % by weight or 0.1 % by weight to 7 % by weight. For example, based on total repeating units, the second copolymer can include the repeating unit of acrylonitrile with an amount of 5 % by weight to 60 % by weight, 10 % by weight to 50 % by weight or 20 % by weight to 40 % by weight. The second copolymer can include the repeating unit of styrene with an amount of 5 % by weight to 50 % by weight, 10 % by weight to 40 % by weight or 20 % by weight to 30 % by weight.
[0048] In another example, the second thermoplastic resin may include a phenoxy-based resin such as bisphenol A type phenoxy resin, bisphenol F type phenoxy resin, bisphenol A / F type phenoxy resin, and fluorene-based phenoxy resin. Commercially available phenoxy-based resins such as YP-50 (from Kukdo Chemical) may be used.
[0049] The second thermoplastic resin may have a weight average molecular weight of 10,000 g / mol to 1,000,000 g / mol.
[0050] The glass transition temperature of the second thermoplastic resin may be higher than 50° C., 55° C. or higher, or 60° C. or higher, and 100° C. or lower, 90° C. or lower, 85° C. or lower, 80° C. or lower, 75° C. or lower, or 70° C. or lower. Within this range, it can be combined with the first thermoplastic resin, allowing the Y value in Equation 1 to have a lower value.
[0051] Based on the total solid content of the adhesive layer, the thermoplastic resin may be included in an amount of 1 wt % to 30 wt %. Specifically, based on the total solid content of the adhesive layer, the thermoplastic resin may be included in an amount of 1 wt % or more, 3 wt % or more, 5 wt % or more, or 7 wt % or more, and 30 wt % or less, 20 wt % or less, 15 wt % or less, or 12 wt % or less. Within this range, it is advantageous to provide an adhesive layer in which a semiconductor element can be embedded without generating voids during semiconductor manufacturing.
[0052] The first thermoplastic resin and the second thermoplastic resin may be included in a weight ratio of 1:10 to 1:0.1, 1:5 to 1:0.2, 1:2 to 1:0.5, or 1:1.2 to 1:0.8. Within this range, it is advantageous to provide an adhesive layer in which Y in Equation 1 is 3 or less.
[0053] Thermosetting resins can react with curing agents to exhibit heat resistance or mechanical strength.
[0054] Thermosetting resin can include epoxy resin. The type of epoxy resin is not particularly limited, but can include one or more resins selected from the following: cresol novolac epoxy resin, bisphenol F type epoxy resin, bisphenol F type novolac epoxy resin, bisphenol A type epoxy resin, bisphenol A type novolac epoxy resin, phenol novolac epoxy resin, tetrafunctional epoxy resin, biphenyl type epoxy resin, biphenyl type novolac epoxy resin, trisphenol methane type epoxy resin, alkyl-modified trisphenol methane type epoxy resin, naphthalene type epoxy resin, dicyclopentadiene type epoxy resin, dicyclopentadiene-modified phenol type epoxy resin, glycidylamine type epoxy resin and alicyclic epoxy resin.
[0055] Thermosetting resins may include liquid epoxy resins and solid epoxy resins. In this case, the resin can easily adjust the curing degree of the adhesive layer, can further improve the bonding performance, and has appropriate fluidity, which can be beneficial to allow Y in equation 1 to have a value of 3 or less.
[0056] The liquid epoxy resin is not particularly limited in terms of its physical properties, but, for example, may have a viscosity of 500 to 20,000 mPa·sec at 25° C. The epoxy equivalent weight of the liquid epoxy resin may be 100 to 1000 g / equivalent.
[0057] The solid epoxy resin is not particularly limited in terms of its physical properties, but may have, for example, a softening point of 50° C. to 120° C. The solid epoxy resin may have an epoxy equivalent weight of 100 g / equivalent to 1000 g / equivalent.
[0058] Based on the total solid content of the adhesive layer, the thermosetting resin may be included in an amount of 5 wt % to 50 wt %. Specifically, based on the total solid content of the adhesive layer, the thermosetting resin may be included in an amount of 5 wt % or more, 10 wt % or more, or 15 wt % or more, and 50 wt % or less, 40 wt % or less, or 35 wt % or less. Within this range, it is advantageous to provide an adhesive layer in which a semiconductor element can be embedded without generating voids during semiconductor manufacturing.
[0059] The liquid epoxy resin and the solid epoxy resin may be included in a weight ratio of 1:10 to 1:0.1, 1:5 to 1:0.2, 1:2 to 1:0.5, or 1:2 to 1:1.2. Within this range, the adhesive layer has sufficient adhesion to the semiconductor element and is advantageously provided in which Y in Equation 1 is 3 or less.
[0060] The type of curing agent is not particularly limited, but may include, for example, at least one of an amine-based compound, an anhydride-based compound, an amide-based compound, and a phenol-based compound. Specifically, the amine-based compound may be one or more selected from the following: diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, diaminodiphenylsulfone, and isophoronediamine. The anhydride-based compound may be one or more selected from the following: phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride. The amide-based compound may be a polyamide resin synthesized from a dimer of dicyandiamide, linolenic acid, and ethylenediamine. The phenol-based compound can be a polyphenol such as bisphenol A, bisphenol F, bisphenol S, fluorene bisphenol and terpene diphenol; a phenol resin obtained by condensing a phenol with an aldehyde, a ketone, or a diene; a modified product of a phenol and / or a phenol resin; a halogenated phenol such as tetrabromobisphenol A and a brominated phenol resin; other imidazoles, BF3-amine complexes, guanidine derivatives. By selecting a curing agent from those listed above, the degree of curing of the thermosetting resin can be adjusted and the mechanical properties of the adhesive can be improved.
[0061] In one example, the curing agent may include a phenol-based compound. The softening point of the phenol-based compound may be 60° C. or higher, 80° C. or higher, or 100° C. or higher and 160° C. or lower, or 150° C. or lower. The phenol-based compound having a softening point within this range allows the adhesive layer to have a higher tensile modulus at room temperature and has flow characteristics that are conducive to embedding semiconductor elements.
[0062] Based on the total solid content of the adhesive layer, the curing agent may be included in an amount of 1 wt % to 30 wt %. Specifically, based on the total solid content of the adhesive layer, the curing agent may be included in an amount of 1 wt % or more, 5 wt % or more, or 10 wt % or more, and 30 wt % or less, 25 wt % or less, or 20 wt % or less. Within this range, the phenomenon that the adhesive layer flows during the semiconductor manufacturing process can be prevented, and the generation of voids can be effectively prevented.
[0063] The type of inorganic filler is not particularly limited, but may include, for example, one or more selected from the following: silicon dioxide, titanium dioxide, aluminum hydroxide, calcium carbonate, magnesium hydroxide, aluminum oxide, talc, and aluminum nitride. By using the above-mentioned types of inorganic fillers, the adhesion of the adhesive layer can be improved and cracks in the semiconductor package can be prevented.
[0064] The average particle size of the inorganic filler may be 0.03 μm to 3 μm. Specifically, the average particle size of the inorganic filler may be 0.04 μm or more, or 0.05 μm or more, and 2.5 μm or less, or 2 μm or less. When the average particle size of the inorganic filler is within the above-mentioned range, the degree of dispersion of the inorganic filler in the adhesive layer may be increased.
[0065] Based on the total solid content of the adhesive layer, the inorganic filler may be included in an amount of 20 wt % to 60 wt %. Specifically, based on the total solid content of the adhesive layer, the inorganic filler may be included in an amount of 20 wt % or more, 30 wt % or more, or 35 wt % or more, and 60 wt % or less, 55 wt % or less, or 50 wt % or less. Within this range, the mechanical properties of the adhesive layer can be improved, the mismatch of the thermal expansion coefficient with the semiconductor chip can be reduced, and the reliability can be improved.
[0066] The adhesive layer may further include a curing catalyst. Specifically, the curing catalyst may be selected from one of the following: a phosphorus-based compound, a boron-based compound, a phosphorus-boron-based compound, an imidazole-based compound, and a combination thereof, but is not limited thereto. By using a curing catalyst, the effect of the curing agent and the curing of the adhesive layer may be promoted. In addition, the amount of the curing catalyst used may be appropriately selected in consideration of the physical properties of the adhesive layer to be ultimately manufactured.
[0067] If necessary, the adhesive layer may further include known additives, such as a coupling agent, a leveling agent, a dispersant, or a combination thereof.
[0068] The thickness of the adhesive layer can vary depending on the height of the semiconductor element to which the non-conductive film is applied. As non-limiting examples, the thickness of the adhesive layer can be controlled to be 1 μm or more, or 5 μm or more and 500 μm or less, 100 μm or less, or 50 μm or less.
[0069] On the other hand, according to another embodiment of the present invention, there is provided a semiconductor device including a non-conductive film and a semiconductor element, wherein the semiconductor element is embedded through an adhesive layer. The non-conductive film may be the non-conductive film according to the above embodiment.
[0070] The type of the semiconductor element is not particularly limited, but may include, for example, bumps that can be used in a flip chip mounting method.
[0071] A semiconductor device of another embodiment can be manufactured by forming an adhesive layer on the bump forming surface of a semiconductor element or attaching the adhesive layer thereto, performing a cutting process if necessary, and then mounting the semiconductor element at a position to be connected, and metal bonding and sealing can be performed simultaneously using a thermocompression bonding method.
[0072] As mentioned above, when the value of Y calculated by Equation 1 is 3 or less, voids are not easily generated even when the adhesive layer is applied to the thermocompression bonding method, and electrodes with a fine pitch can also be effectively embedded to provide a semiconductor device with excellent reliability.
[0073] On the other hand, according to another embodiment of the present invention, a method for manufacturing a semiconductor device is provided, the method comprising the following steps: calculating Y in Equation 1 for a non-conductive film including an adhesive layer, and selecting a non-conductive film including an adhesive layer in which Y is greater than 0 and is 3 or less; and applying the selected non-conductive film to an element forming surface of a semiconductor element.
[0074] As mentioned above, when a non-conductive film including an adhesive layer in which Y calculated by Equation 1 is 3 or less is used in a semiconductor manufacturing process, voids are not easily generated and electrodes with a fine pitch can also be effectively embedded to provide a semiconductor device with excellent reliability.
[0075] In the semiconductor device manufacturing method, Y in Equation 1 is calculated before the semiconductor device manufacturing process to predict in advance whether voids will occur in the non-conductive film, and a non-conductive film that is less likely to generate voids can be selected and applied to the semiconductor manufacturing process.
[0076] In one example, in a semiconductor device manufacturing method, a non-conductive film may be prepared in the form of a die bonding film in which an adhesive layer is laminated on a substrate, or a dicing die bonding film in which a pressure-sensitive adhesive layer and an adhesive layer are sequentially laminated on a substrate. Then, the adhesive layer is attached to the element forming surface of the semiconductor element, and if the non-conductive film is a dicing die bonding film, a dicing process is performed, and the semiconductor element is mounted at a position to be connected, and metal bonding and sealing are simultaneously performed using a thermocompression bonding method, thereby enabling the manufacture of a semiconductor device.
[0077] In another example, in a method for manufacturing a semiconductor device, the above-mentioned adhesive layer may be formed on an element forming surface of a semiconductor element to form a non-conductive film. Then, after undergoing a cutting process as needed, the semiconductor element may be mounted at a position to be connected, and a thermal compression bonding method may be used to simultaneously perform metal bonding and sealing to manufacture a semiconductor device.
[0078] The conditions of the thermocompression bonding process are not particularly limited. In one example, the thermocompression bonding process may be performed by applying a pressure of 30N to 150N at a temperature of about 50°C to 150°C for 2 seconds to 10 seconds, and then heating at a temperature of about 200°C to 300°C for 2 seconds to 10 seconds.
[0079] By Equation 1, the non-conductive film used in the semiconductor device manufacturing method is selected to be less likely to generate voids, and therefore, even if the thermocompression bonding process is performed under the above conditions, voids are not easily generated, making it possible to provide a semiconductor device with excellent reliability.
[0080] Beneficial Effects
[0081] The non-conductive film according to an embodiment can effectively prevent the generation of voids during a semiconductor manufacturing process and sufficiently adhere to a semiconductor element to provide a semiconductor device having excellent reliability. DETAILED DESCRIPTION
[0082] Hereinafter, the action and effect of the present invention will be described in more detail with reference to specific embodiments of the present invention. However, these embodiments are presented for illustrative purposes only, and the scope of the present invention is not limited thereby in any way.
[0083] Preparation Example 1: Preparation of thermoplastic resin
[0084] 59 g of n-butyl acrylate, 10 g of acrylonitrile, 3 g of glycidyl methacrylate, and 28 g of isobutyl methacrylate were added to 100 g of toluene. Then, the obtained reaction product was reacted at 80° C. for about 12 hours to synthesize an acrylate-based resin (weight average molecular weight: about 500,000, glass transition temperature: -5° C.) into which a glycidyl group was introduced.
[0085] Preparation Example 2: Preparation of thermoplastic resin
[0086] 40 g of n-butyl acrylate, 25 g of ethyl acrylate, 30 g of acrylonitrile and 5 g of glycidyl methacrylate were added to 100 g of toluene. Then, the obtained reaction product was reacted at 80° C. for about 12 hours to synthesize an acrylate-based resin (weight average molecular weight: about 500,000, glass transition temperature: 40° C.) into which a glycidyl group was introduced.
[0087] Preparation Example 3: Preparation of thermoplastic resin
[0088] 40 g of butyl acrylate, 30 g of acrylonitrile, 5 g of glycidyl methacrylate and 25 g of styrene were added to 100 g of toluene. Then, the obtained reaction product was reacted at 80° C. for about 12 hours to synthesize an acrylate-based resin (weight average molecular weight: about 700,000, glass transition temperature: 63° C.) into which a glycidyl group was introduced.
[0089] Preparation Example 4: Preparation of thermoplastic resin
[0090] 35 g of a phenoxy resin (Kukdo Chemical YP-50, weight average molecular weight: about 55,000, glass transition temperature: 80° C. to 83° C.) was dissolved in 65 g of toluene to prepare a thermoplastic resin.
[0091] Example 1: Fabrication of non-conductive film and semiconductor device
[0092] (1) Preparation of adhesive composition
[0093] The components listed in the following Table 1 were added to methyl ethyl ketone in the amounts shown in Table 1 and mixed to prepare an adhesive composition (solid content: 50% by weight).
[0094] (2) Manufacturing of non-conductive films
[0095] The adhesive composition was applied onto a release-treated polyethylene terephthalate film (38 μm in thickness) using a comma coater and then dried at 110° C. for 3 minutes to form a B-stage adhesive layer having a thickness of about 20 μm.
[0096] (3) Manufacturing of semiconductor devices
[0097] A semiconductor element having a plurality of through silicon vias was prepared. Bumps were formed in the semiconductor element in which lead-free solder (SnAgCu) was formed to a height of 3 μm on a copper filler having a height of 15 μm and a pitch of 50 μm.
[0098] The non-conductive film was positioned so that the adhesive layer was in contact with its surface on which the bumps were formed, and then vacuum lamination was performed at 80° C. Then, the polyethylene terephthalate film was peeled off from the adhesive layer.
[0099] Subsequently, the substrate and the semiconductor element were arranged so that the bumps of the semiconductor element were positioned on the connection pads of the substrate having connection pads with a pitch of 50 μm. Then, using a thermocompression bonding machine, the laminate of the substrate and the semiconductor element was pressed at 100 N at 70°C for 3 seconds and then heated to 260°C for 4 seconds for thermocompression bonding.
[0100] Examples 2 to 4 and Comparative Examples 1 to 3: Production of non-conductive films and semiconductor devices
[0101] An adhesive composition, a non-conductive film, and a semiconductor device were manufactured in the same manner as in Example 1, except that the composition of the adhesive composition of Example 1 was changed as shown in Table 1 below.
[0102] [Table 1]
[0103]
[0104] The contents (parts by weight) in Table 1 are solid contents.
[0105] RE-310S: Liquid epoxy resin (Nippon Kayaku Co., Ltd., bisphenol A type epoxy resin, epoxy equivalent weight 180 g / equivalent)
[0106] EOCN-1020-70: solid epoxy resin (Nippon Kayaku Co., Ltd., cresol novolac type epoxy resin, epoxy equivalent weight 199 g / equivalent, softening point: 70°C)
[0107] KA-1165: Phenolic resin (manufactured by DIC, bisphenol A phenolic resin, hydroxyl equivalent weight 119 g / equivalent, softening point: 125°C)
[0108] GPH-103: phenol resin (Nippon Kayaku Co., Ltd., hydroxyl equivalent weight 230 g / equivalent, softening point: 103°C)
[0109] SC-2050: Spherical silica, Admatec, average particle size about 400nm
[0110] 2P4MHZ: 2-phenyl-4-methyl-5-hydroxymethylimidazole
[0111] KBM-403: Silane coupling agent (manufactured by Shin-Etsu, 3,3-glycidoxypropyltrimethoxysilane)
[0112] Test example: Evaluation of physical properties of non-conductive films and performance of semiconductor devices
[0113] (1) Difference between the heat generation starting temperature and the maximum heat generation temperature of the adhesive layer (△T)
[0114] The heat generation onset temperature and the maximum heat generation temperature of the adhesive layer were determined by differential scanning calorimetry (DSC).DSC analysis was performed at a heating rate of 10°C / min and a temperature range of 30°C to 300°C.
[0115] As a result of DSC analysis, a thermogram was obtained in which the horizontal axis is represented by temperature and the vertical axis is represented by heat flow. In the thermogram, the starting point (starting point) where the extended line of the heat generation peak meets the base line is defined as the heat generation starting temperature, and the top of the heat generation peak is defined as the maximum heat generation temperature.
[0116] (2) Gel time of adhesive layer (G)
[0117] The gel time of the B-stage adhesive layer is measured on a hot plate at 200°C. Specifically, the adhesive layers are overlapped and laminated until the thickness reaches 120 μm, and then pressed using a roller laminator at 60°C. The test piece thus obtained is cut into a circle with a diameter of 10 mm. The cut test piece is placed on a hot plate at 200°C and stirred with a stirring rod so that a small circle is drawn on the surface of the test piece. Stirring is continued until the viscosity of the test piece increases and eventually gels, losing fluidity. The time from the time point when the test piece is placed on the hot plate until the test piece gels and loses its fluidity is measured in seconds. Such measurements are performed twice, and if the difference between the two measured values is within 10% of the lower value of the measured value, the gel time is recorded as the average of the two measurements, and if it exceeds 10%, three measurements are performed and the gel time is recorded as the average of the three measurements.
[0118] (3) Minimum melt viscosity of adhesive layer (η)
[0119] The adhesive layers were overlapped and laminated until the thickness reached 400 μm, and then pressed at 60° C. using a roll laminator. The test piece thus obtained was cut into a circle with a diameter of 20 mm. The viscosity of the cut test piece was measured using a MARS device from HAKKE under the conditions of 1000 Pa and a heating rate of 10° C. / min. The lowest viscosity value among the measured viscosity values was defined as the minimum melt viscosity.
[0120] (4) Mold gap test
[0121] By IR microscopy, if the area occupied by the void between the semiconductor element and the substrate was 3% or less, it was evaluated as acceptable (O), and if the area exceeded 3%, it was evaluated as unacceptable (X).
[0122] (5) Evaluation of conduction
[0123] If a daisy chain connection can be determined, the semiconductor device is evaluated as acceptable (0), and if the daisy chain connection cannot be determined, it is evaluated as unacceptable (×).
[0124] (6) Evaluation of connection status
[0125] The semiconductor device was polished so that the cross section of the connection portion was exposed, and the exposed cross section of the connection portion was observed using an optical microscope. If no trap of the adhesive composition was observed in the connection portion and the solder was fully wetted on the wiring, it was evaluated as acceptable (O), otherwise it was evaluated as unacceptable (X).
[0126] (7) Evaluation of fillet gap
[0127] After the semiconductor device was connected by a thermal compression bonding process, the fillet formed at the edge of the semiconductor element was determined using an IR microscope, and if there was no void with an inner diameter of 1 μm or more in the fillet, it was evaluated as acceptable (0), and if there was a void with a diameter of 1 μm or more in the fillet, it was evaluated as unacceptable (×).
[0128] [Table 2]
[0129]
[0130]
[0131] In Table 2, Y is a value calculated by the above-mentioned Equation 1.
[0132] Referring to Table 2, it was determined that in the case of Examples 1 to 4 where Y calculated by Equation 1 was 3 or less, the generation of voids in the fillet formed between the substrate and the semiconductor element or at the edge of the semiconductor element could be suppressed, thereby providing a semiconductor device having an excellent metal connection state. On the other hand, it was determined that in the case of Comparative Examples 1 to 3 where Y calculated by Equation 1 exceeded 3, voids were generated in the fillet formed between the substrate and the semiconductor element and at the edge of the semiconductor element, resulting in a poor metal connection state.
Claims
1. A non-conductive film, comprising: an adhesive layer, the adhesive layer comprising a thermoplastic resin, a thermosetting resin, a curing agent and an inorganic filler, wherein Y of the following equation 1 of the adhesive layer is greater than 0 and is 3 or less: [Equation 1] Y=(△T*G) 2 / (5.88*η) Where, in equation 1, ΔT is the difference between the heat generation starting temperature and the maximum heat generation temperature of the adhesive layer measured by differential scanning calorimetry at a heating rate of 10°C / min and a temperature of 30°C to 300°C, G is the gel time at 200°C measured in seconds for the adhesive layer, and η is the minimum melt viscosity measured in Pa·seconds for the adhesive layer. 2 . The non-conductive film according to claim 1 , wherein ΔT in Equation 1 is 1° C. to 20° C. The non-conductive film according to claim 1 , wherein G in Equation 1 is 5 seconds to 30 seconds. 4 . The non-conductive film according to claim 1 , wherein η in Equation 1 is 10 Pa·sec to 5000 Pa·sec. 5 . The non-conductive film according to claim 1 , wherein the thermoplastic resin comprises two or more types of thermoplastic resins having different glass transition temperatures. The non-conductive film of claim 1 , wherein the thermoplastic resin comprises a first thermoplastic resin having a glass transition temperature of −10° C. to 50° C. and a second thermoplastic resin having a glass transition temperature of more than 50° C. and 100° C. or less. 7 . The non-conductive film of claim 6 , wherein the first thermoplastic resin comprises a first copolymer derived from C1-12 alkyl (meth)acrylate, (meth)acrylate containing an epoxy group, and acrylonitrile.
8. The non-conductive film according to claim 6, wherein the second thermoplastic resin comprises a second copolymer produced from C1-12 alkyl (meth)acrylate, (meth)acrylate containing an epoxy group, acrylonitrile, and styrene; or one or more phenoxy-based resins selected from bisphenol A type phenoxy resin, bisphenol F type phenoxy resin, bisphenol A / F type phenoxy resin and fluorene-based phenoxy resin. 9 . The non-conductive film of claim 6 , wherein the first thermoplastic resin and the second thermoplastic resin are included in a weight ratio of 1:10 to 1:0.
1. 10 . The non-conductive film of claim 1 , wherein the thermosetting resin comprises a liquid epoxy resin and a solid epoxy resin.
11. A semiconductor device comprising the non-conductive film according to claim 1 and a semiconductor element, The semiconductor element is embedded through the adhesive layer. 12 . The semiconductor device according to claim 11 , wherein the semiconductor element comprises a bump.
13. A method for manufacturing a semiconductor device, the method comprising the steps of: Calculating Y in the following Equation 1 for the non-conductive film including the adhesive layer, and selecting the non-conductive film including the adhesive layer in which Y is greater than 0 and 3 or less; as well as Applying the selected non-conductive film to the element-forming surface of the semiconductor element: [Equation 1] Y=(△T*G) 2 / (5.88*η) Where, in equation 1, ΔT is the difference between the heat generation starting temperature and the maximum heat generation temperature of the adhesive layer measured by differential scanning calorimetry at a heating rate of 10°C / min and a temperature of 30°C to 300°C, G is the gel time at 200°C measured in seconds for the adhesive layer, and η is the minimum melt viscosity measured in Pa·seconds for the adhesive layer.
